Construction of stereocomplex granular dams in luminescent biopolymer systems. Issue 44 (20th October 2020) - Yin, Zhenzhong; Wang, Chuanfeng; Peng, Zhou; Huang, Xi; Li, Wei; Shao, Dingyun; Zhang, Chaoliang; Lu, Jun
Abstract : Lessons from natural and artificial granular dams inspired the design of dam structures of stereocomplex granules in multicolor emissive biopolymer systems. Abstract : The accelerated but controlled environmental degradation of luminescent stereocomplex (sc) biopolymers is particularly desirable in reliable biological applications. Nevertheless, it still remains a huge challenge to date. In this work, inspired by natural and artificial granular dams, we report for the first time the controllable in situ construction of dam structures of crystalline sc granules in enantiomeric polylactides (PLAs) with the assistance of fluorescent carbon quantum dots (CQDs) at high pressure. The embedding of guest CQD assemblies into the host matrices of PLAs endows the pressure processed PLA/CQD biosystems with intriguing color tunable fluorescence emission. Also, the CQD assembled nanoparticles effectively regulate the size, distribution, stacking and hierarchical architecture of the granular stereocomplexes in the granulated sc dams. Consequently, different structures of stereocomplex granular dams are constructed spontaneously in the matrices of the PLA/CQD materials by varying high pressure crystallization conditions. This allows for the flexible and efficient control of the rate of diffusion of water in the biosystems, and further leads to the fabrication of a multicolor emissive biocomposite with an increasable but controllable hydrolytic degradation rate. The present study may offer a new perspective for the structural design of novel stereocomplex biomedical materials with well-defined textures.